Convenient Cr(VI) Removal from Aqueous Samples: Executed by a Promising Clay‐Based Catalytic System, Magnetized by Fe3O4 Nanoparticles and Functionalized with Humic Acid. Issue 8 (24th February 2020) - Hajizadeh, Zoleikha; Valadi, Kobra; Taheri‐Ledari, Reza; Maleki, Ali
Abstract: Here, a nanoscale efficient adsorbent for chromium(VI) ion is presented, which is constructed of halloysite nanotubes (HNTs) as a natural basis. On the other hand, to add magnetic property, iron oxide (Fe3 O4 ) nanoparticles have been incorporated inside and leaded onto the surface of HNTs. As the main component of nanoabsorbent, humic acid (HA) is also loaded onto the surface of HNT/Fe3 O4 nanocomposite. Cr(VI) removal process has been carefully monitored in the presence of the fabricated HNT/Fe3 O4 ‐HA nanoabsorbent from aqueous solutions with different concentrations of K2 CrO4 . The adsorption isotherms are interpreted by Langmuir graphs, and 98% removal efficiency (RE) has been obtained at room temperature, in 15 min contact time. Additionally, all the analyses related to the structure of desired product have been done, and the recyclability of produced nanoabsorbent is precisely investigated, as well. Abstract : An efficient adsorbent system for chromium(VI) ion constructed of halloysite nanotubes (HNTs), iron oxide (Fe3 O4 ) nanoparticles functionalized with humic acid (HA) in nanoscale is presented. Chromium(VI) removal process from aqueous solutions has been carefully screened in the presence of this novel fabricated nanoabsorbent by using K2 CrO4 solutions in different concentrations. The adsorption isotherms are interpreted by Langmuir graphs, and 98% removal efficiency (RE) has been obtained at room temperature, in 15 min contact time.